A slippery slope for Cryogenian diamictites?. (27th March 2019) - Le Heron, Daniel Paul; Vandyk, Thomas M.
Abstract: The Death Valley region has previously been claimed to preserve the sedimentary records of both the Sturtian and Marinoan snowball Earth events within the Kingston Peak Formation, which outcrops in a number of disconnected mountain ranges. In this context, new sedimentary logs are presented together with detailed clast textural analyses which allow diamictites of the Alexander Hills and the Saddle Peak Hills to be compared in detail for the first time, and to be contrasted with rocks of well‐established glaciogenic origin from the Kingston Range. Notably, in the Saddle Peak Hills, clasts identical in composition and facies to that of the Noonday Dolomite—a unit previously interpreted as the post‐Marinoan cap carbonate—are incorporated into diamictites at the top of the Kingston Peak Formation. Combined with the carbonate‐rich composition of rocks at the top of the formation, these observations suggest that the uppermost diamictites of the Saddle Peak Hills and Alexander Hills are genetically related to the Noonday Dolomite and are unrelated to glacial processes. We propose that they formed through local slope foundering and basinward collapse of the adjacent carbonate platform, substantiating recent interpretations of Noonday carbonate platform dynamics, and demonstrating that they are genetically unrelated to Cryogenian glaciation. Thus, clast textural analyses play a valuable role in establishing whether contested 'snowball Earth' outcrops are truly glaciogenic or simply the product of local slope collapse. Abstract : Using the Cryogenian rocks of Death Valley as a study area, we re‐evaluate diamictites long thought to be 'glacial' in character. Whilst some certainly are (highly variable clast types, striated, commonly associated with dropstones), others originate from slope collapse and are completely unrelated to glaciation. This has major implications for models viewing diamictites as important regional, or indeed transcontinental, chronostratigraphic markers in the Cryogenian.